Pengaruh Motivasi Dan Pelatihan Terhadap Kinerja Karyawan CU Sauan Sibarrung Kabupaten Tana Toraja - Kannapadang, Dwibin (Jurnal Ekonomi, Bisnis dan Terapan (JESIT), 2021)
This study aims to determine the effect of motivation on employee performance, to determine the effect of training on employee performance and to dterminethe affect of motivation and training on employees performance. Tihis research was conducted at the cooperative CU Sauan Sibarrung, Tana Toraja Regency. This population of this study were all employees of CU Sauan Sibarrung, Tana Toraja Regency with a total of 50 employees, and the sampling technique used saturated samples, because all members of the population were used as smples. The data collction technique in this study used a questionnaire with a likert scale measurement. The result showed that motivation has a positive effect on employee performance; training has a positive effect on employee performance; and motivation and training together have a positive effect on employee performance.